The Role of the Amygdala, Retrosplenial Cortex, and Medial Prefrontal Cortex in Trace Fear Extinction and Reconsolidation - (:unkn) unknown (My University, 2013)
A wealth of research has outlined the neural circuits responsible for the consolidation, reconsolidation, and extinction of standard "delay" fear conditioning, in which awareness is not required for learning. Far less is understood about the neural circuit supporting more complex, explicit associations. "Trace" fear conditioning is considered to be a rodent model of explicit fear because it relies on the cortex and hippocampus and requires explicit contingency awareness in humans for successful acquisition. In the current set of studies, we aimed to better characterize the neural circuit supporting the consolidation, reconsolidation, and extinction of trace fear in order to better understand how explicit associations are stored and updated in the brain. We found that trace fear extinction relies on NMDA receptors in the retrosplenial cortex and prelimibic medial prefrontal cortex, rather than the amygdala, which is required for extinguishing delay fear. NMDA receptors in the infralimbic medial prefrontal cortex, on the other hand, were involved in the extinction of both delay and trace associations. These results suggest that trace fear is consolidated and stored in a distributed cortical manner, relying in part on the retrosplenial and prelimbic cortices. The amygdala, on the other hand, is responsible for the long-term storage of delay, but not trace associations. Consistent with this, our next study demonstrated that protein synthesis in the retrosplenial cortex was required for the acquisition or early consolidation of trace, but not delay fear. Finally, we demonstrated that a reconsolidation-dependent updating procedure can be used to shift a relatively complex trace fear association to the more basic neural circuit that supports delay fear. Together, these results provide a more complete understanding of the neural circuit supporting trace fear, demonstrating that this type of complex association relies on multiple cortical structures for extinction, including the retrosplenial and prelimbic cortices, instead of the amygdala. Our results also demonstrate that updating procedures can reorganize the neural circuit supporting a complex trace fear memory so that the association relies on a simpler set of structures.
Keywords: Extinction; Fear Conditioning; Prefrontal Cortex; Reconsolidation; Retrosplenial Cortex; Trace Fear